Issledovanie voleboj aktivnosti v strukture individualnosti sportsmena - Gorbunov, Yu. Ya. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The study aimed at two problems: 1. Analysis of the role of will activities in the integral individuality of athletes in different kinds of sport, 2. Analysis of special influence factors on the character of will activities in different sports.